Ground response analysis for stiff and soft soil under different earthquake events: a comparison - Mazlina, M. (2021)
This research work focusing on site ground response analysis of stiff and soft soil from several sites in Peninsular Malaysia Operation based on PETRONAS offshore region classification. The main purpose is to determine how these sites will react under seismic loading in terms of peak surface acceleration, response spectra and soil amplification factor under different earthquake events. A developed 1 Dimensional nonlinear analysis program known as NERA, were adopted to analyse layered soil deposits to predict site response. Six sites in peninsular Malaysian water which are classified as stiff and soft soil were analysed using six earthquake events based on time history for 1000 years return period. Findings show that, amplification occur between predicted bedrock and seabed which increased the amount of vibration received by seabed as well as offshore facilities.